A fast exploration of very deep soil layers by Eucalyptus seedlings and clones in Brazil - Pinheiro, Rafael Costa [UNESP]; Deus, Jose Carlos de [UNESP]; Nouvellon, Yann; Campoe, Otavio Camargo; Stape, Jose Luiz; Alo, Livia Lanzi; Guerrini, Irae Amaral [UNESP]; Jourdan, Christophe; Laclau, Jean-Paul [UNESP] (Elsevier B.V., 2016)
Although pioneer studies showed several decades ago that deep rooting is common in tropical forests, direct measurements of fine root distributions over the entire soil profile explored by the roots are still scarce. Our study aimed to compare, 2 years after planting, fine root traits of Eucalyptus trees planted from cuttings and from seedlings in order to assess whether the propagation mode has an influence on the capacity of the trees to explore very deep soils. Soils cores were sampled down to a depth of 13.5 mat the peak of leaf area index (LAI), 2 years after planting, under three Eucalyptus clones (belonging to species E. saligna, E. grandis x E. urophylla, E. grandis x E. camaldulensis) and under E. grandis seedlings in the same Ferralsol soil. LAI was estimated using allometric equations based on destructive sampling of eight trees per genotype. All the genotypes exhibited fine root densities roughly constant between the depths of 0.25 and 6.00 m. Changes in fine root traits (diameter, specific root length and specific root area) were low between the topsoil and the root front. The ratios between mean tree height and root front depth ranged from 0.8 to 1.2 for the four genotypes. Although tree vertical extension was roughly symmetric above and below ground for all the genotypes, the depth of the root front ranged from 8.0 m for the seedlings and the E. grandis x E. urophylla clone to 11.5 m for the E. saligna clone. Soil water content profiles suggested that the four genotypes had the capacity to withdraw water down to a depth of 8-10 m over the first 2 years after planting. Total fine root length ranged from 3.3 to 6.0 km per m(2) of soil depending on the genotype. The root area/leaf area ratio ranged from 1.3 to 3.2 and was negatively correlated with LAI across the four genotypes. This pattern suggests that the genotypes more conservative for water use (with a low LAI) invest more in fine root area relative to leaf area than genotypes adapted to wet regions (with a high LAI). The velocity of downward movement of the root front might be a relevant criterion in the last stage of the breeding programs to select clones with a fast exploration of deep soil layers in drought prone regions. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: Eucalypt; Fine root; Breeding; Leaf area; Root area; Tropical soil